2015
DOI: 10.1093/ije/dyv296
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of ambient temperature and diarrhoeal diseases

Abstract: Changes in temperature due to global climate change can and may already be affecting diarrhoeal disease incidence. The vulnerability of populations may depend, in part, on local pathogen distribution. However, evidence of publication bias and the uneven geographical distribution of studies limit the precision and generalizability of the pooled estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
130
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(171 citation statements)
references
References 61 publications
(52 reference statements)
15
130
2
4
Order By: Relevance
“…In particular, studies have shown increases in diarrhea incidence of 3–11%, per degree Celsius ambient temperature increase in Fiji (Singh et al, 2001), Bangladesh (Hashizume et al, 2007), Peru (Checkley et al, 2000; Lama et al, 2004) and Japan (Onozuka et al, 2010). These regional results are corroborated by a recent global meta-analysis indicating a 7% increase in all-cause diarrhea per degree Celsius temperature increase based on the 10 studies that met the inclusion criteria (Carlton et al, 2015). While some of this research has shown a linear relationship between temperature and diarrhea rates (Hashizume et al, 2007), these associations can be non-linear and depend on local climatic conditions and pathogens.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In particular, studies have shown increases in diarrhea incidence of 3–11%, per degree Celsius ambient temperature increase in Fiji (Singh et al, 2001), Bangladesh (Hashizume et al, 2007), Peru (Checkley et al, 2000; Lama et al, 2004) and Japan (Onozuka et al, 2010). These regional results are corroborated by a recent global meta-analysis indicating a 7% increase in all-cause diarrhea per degree Celsius temperature increase based on the 10 studies that met the inclusion criteria (Carlton et al, 2015). While some of this research has shown a linear relationship between temperature and diarrhea rates (Hashizume et al, 2007), these associations can be non-linear and depend on local climatic conditions and pathogens.…”
Section: Discussionsupporting
confidence: 59%
“…The aforementioned recent meta-analysis found that the relationship between temperature and all-cause diarrhea was not modified by either geographical climate category or national income group. However, for bacterial diarrhea, there was a stronger effect size between temperature and diarrhea for low and middle income countries and in tropical climates (Carlton et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analysis was conducted on a subset of studies of temperature and diarrhea that met more rigorous reporting and design criteria; this analysis has been described elsewhere. 22 For studies of heavy rainfall, flooding and drought meta-analysis was not appropriate, according to the Cochrane Collaboration Handbook, because of the disparate analytical methods and exposure definitions applied in these studies. 20 The approach used here allows us to present a semi-quantitative summary of the studies we identified, in order to allow inclusion of the widest range of studies and to avoid selection bias that would result from restricting studies to those with a single exposure and outcome definition.…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding the complex pathways linking climate anomalies and diarrhoea [69] and the challenges this poses for quantifying the effects of weather and climate on water-associated diseases in general [70][71][72], diarrhoeal illness is generally sensitive to climate anomalies [73][74][75][76][77][78] with unusually warm conditions conducive to enhanced pathogen replication and survival rates, while rainfall surpluses may transport faecal matter into water courses with micro-organisms becoming concentrated in water bodies during periods of rainfall deficit. While Demisse and Mengisitie [79] noted that El Niño has an impact on diarrhoea incidence for a number of major geographic regions, many of the cited papers address temperature/rainfall-diarrhoea association as opposed to climate driven variations in diarrhoea moderated by ENSO.…”
Section: Diarrhoeamentioning
confidence: 99%